Micronutrient status, food security, anaemia, Plasmodium infection, and physical activity as predictors of primary schoolchildren's body composition in Côte d'Ivoire - Long, Kurt Z.; Traoré, Sylvain G.; Kouassi, Kouadio B.; Coulibaly, Jean T.; Gba, Bomey C.; Dao, Daouda; Beckmann, Johanna; Lang, Christin; Seelig, Harald; Probst-Hensch, Nicole; Pühse, Uwe; Gerber, Markus; et al. (Frontiers in Nutrition, 2025)
BackgroundStunting and overt malnutrition remain prevalent among school age children in rural areas of Côte d'Ivoire while obesity is increasing in urban areas. Associations of children's nutritional status, Plasmodium infection, physical activity and household characteristics with body composition were analyzed to identify what factors might be contributing to this dual burden of disease.MethodsLongitudinal growth curve models (LGCM) evaluated associations of micronutrient status, household food security, Plasmodium falciparum prevalence and physical activity assessed at three time points with fat free mass and fat mass.ResultsMore severe anaemia was inversely associated with FFM and TrFFM trajectories overall and among girls. P. falciparum infection had an indirect inverse association with FFM trajectories through anaemia among girls and through reductions of vitamin A directly associated with FFM. Changes in zinc concentrations were positively associated with FM trajectories overall and among boys. Food insecurity was inversely associated with FFM among boys from lower socio-economic status (SES) households while increased MVPA was associated with reduced fat mass among girls.ConclusionsThe integration of Malaria control programs with efforts to improve household healthy diet and promote physical activity can lead to improvements in body composition and overall child health and wellbeing.